Process capability analysis in manufacturing titanium dioxide - Nurul Hidayah, Razak (2008)
In this thesis some aspects of process capability analysis are considered. Process capability analysis deals with how to assess the capability of manufacturing processes. Based on the process capability analysis one can determine how the process performs relative to its product requirements or specifications. An important part within process capability analysis is the use of process capability indices. This thesis focuses on process capability analysis in Tioxide (M) Sdn Bhd which is manufacturing titanium dioxide (TiO2). The objectives of this thesis are to asses the current process capability of the process selected and predict the future capability and identify process improvement opportunities that can be applied in the industry. The process capability was analyzed in four parameters control which are grey stage time, precipitation recovery, crystal size & crystal size distribution and particle size & particle size distribution had been performed in order to predict the future capability of the process. It shows that all the process selected was in capable state, except for Grey Stage Time 1 (GST 1) and Grey Stage Time 2 (GST 2) was incapable and need an improvement. Recommendation had been proposed to overcome this state. Finally, it is hope that this thesis could contribute knowledge for those people who interested in process capability analysis.